I will explain step by step how to solve for x
Remove the parenthesis using distributive property
1.5(x + 4) - 3 = 4.5(x - 2)
1.5(x) + 1.5(4) = 4.5(x) - 4.5(2)
1.5x + 6 = 4.5x - 9
Combining like-terms. Move the terms whose variable x to the left side, and move constants to the right side. Plus sign will become substract sign after being moved.
1.5x + 6 = 4.5x - 9
1.5x - 4.5x = -9 - 6
-3x = -12
Move -3 to the right side to solve for x. Multiplication becomes division after being moved to the other side
-3x = -12
x = -12/-3
x = 4
The value of x is 4